Lifetime physical activity and the risk of amyotrophic lateral sclerosis. Issue 9 (16th February 2013) - Huisman, Mark H B; Seelen, Meinie; de Jong, Sonja W; Dorresteijn, Kirsten R I S; van Doormaal, Perry T C; van der Kooi, Anneke J; de Visser, Marianne; Schelhaas, Helenius Jurgen; van den Berg, Leonard H; Veldink, Jan Herman
Abstract : Background: It has been hypothesised that physical activity is a risk factor for developing amyotrophic lateral sclerosis (ALS), fuelled by observations that professional soccer players and Gulf War veterans are at increased risk. In a population based study, we determined the relation between physical activity and risk of sporadic ALS, using an objective approach for assessing physical activity. Methods: 636 sporadic ALS patients and 2166 controls, both population based, completed a semistructured questionnaire on lifetime history of occupations, sports and hobbies. To objectively compare the energy cost of a lifetime history of occupational and leisure time physical activities and to reduce recall bias, metabolic equivalent scores were assigned to each activity based on the Compendium of Physical Activities. Results: ALS patients had significantly higher levels of leisure time physical activity compared with controls (OR 1.08, 95% CI 1.02 to 1.14, p=0.008). No significant difference was found between patients and controls in the level of vigorous physical activities, including marathons and triathlons, or in occupational activity. Cumulative measures of physical activity in quartiles did not show a dose–response relationship. Conclusions: An increased risk of ALS with higher levels of leisure time physical activity was found in the present study. The lack of association with occupational physical activity and the absence of a dose–response relationship strengthen the hypothesis that not increased physical activity per se but rather a genetic profile or lifestyle promoting physical fitness increases ALS susceptibility.